Operational control of the parameters of liquid fuels and lubricants with impurities - Zhukov, B.V.; Borbulev, S.I.; Odnovol, A.V. (Radiotekhnika, 2021)
The possibilities of operational control of the parameters of liquid fuels and lubricants with impurities using the resonator method of microwave dielectrometry are considered. Preliminary studies of liquid fuels and lubricants (gasolines, diesel fuels, kerosene, oils) showed that the values ​​of the real and imaginary components of the complex dielectric constant of the listed fuels and lubricants are in the operating range of the resonator microwave dielectrometer. The high resolution of the microwave resonator method determines the prospects of using this method for analyzing the complex dielectric constant of mixtures of fuels and lubricants with various impurities, including water, alcohols, benzene, etc. For a mixture of gasoline with benzene, it was experimentally established that with a small addition of benzene (no more than 15%), an increase in the real component of the complex dielectric constant of the mixture is observed, and with a benzene content exceeding 15%, an increase in both components of the complex dielectric constant of the mixture takes place. The process has also been installed, but the NHF dielectrometer has made it possible to identify the transformer in real time due to the presence of water in the amount of 14, 28 and 56 grams per ton of oil. The research results indicate that the microwave dielectrometry method can be considered promising for monitoring the quality of transformer oil both during the filling process and for monitoring its quality during the operation of high-voltage transformers. The results of the initial stage of research on alcohol gasolines have not yet revealed the predominant effect of the alcohol additive on the location of the experimental points on the complex plane. This circumstance is most likely due to the fact that alcohol gasolines with a close octane number can have a significantly different chemical composition.